Selective enhancement of glutamate-mediated pressor responses after GABAA receptor blockade in the RVLM of sedentary versus spontaneous wheel running rats - Mueller, Patrick J.; Mischel, Nicholas A. (Frontiers in Physiology, 2012)
Overactivity of the sympathetic nervous system (SNS) is a hallmark of many cardiovascular diseases. It is also well-known that physical inactivity independently contributes to cardiovascular diseases, likely in part via increased SNS activity. Recent work from our laboratory has demonstrated increased SNS responses in sedentary animals following either direct activation or disinhibition of the rostral ventrolateral medulla (RVLM), an integral cardiovascular brainstem region. These data led us to hypothesize that the interaction between excitation and inhibition of the RVLM is altered in sedentary versus physically active animals. To test this hypothesis, we recorded mean arterial pressure (MAP) and lumbar sympathetic nerve activity (LSNA) in Inactin anesthetized rats that were housed for 8–12 weeks with or without access to a running wheel. Pressor responses to direct activation of the RVLM with glutamate were similar between groups under intact conditions. However, blockade of γ-aminobutyric acid (GABA)A receptors with bicuculline selectively enhanced pressor responses to glutamate in sedentary animals. Interestingly, LSNA responses to glutamate were not enhanced in sedentary versus active animals in the presence or absence of tonic GABAergic tone. These results suggest that sedentary compared to active conditions enhance GABAergic inhibition of glutamate-sensitive neurons in the RVLM that are involved in blood pressure regulation, and by mechanisms that do not involve LSNA. We also speculate that regular physical activity has differential effects on SNS activity to specific vascular beds and may reduce the risk of developing cardiovascular diseases via changes occurring in the RVLM.